Evaluation of groundwater potential in Kabirwala area, Pakistan: A case study by using geophysical, geochemical and pump data. (7th September 2018) - Hasan, Muhammad; Shang, Yanjun; Akhter, Gulraiz; Jin, Weijun
ABSTRACT: Knowledge of hydraulic parameters (hydraulic conductivity and transmissivity) is essential for the delineation of groundwater potential zones. Conventionally, these parameters are measured using pumping tests carried out on boreholes. However, pumping tests are costly, labour intensive and require a considerable amount of equipment. The integration of geophysical methods with pumping tests provides efficient and cost‐effective alternative to calculate hydraulic parameters. Fifty electrical resistivity soundings were carried out in the study area using Schlumberger inter‐electrode configuration to obtain hydraulic characteristics that are estimated through the pumping tests. To apply this approach successfully, sufficient number of boreholes are used. Part of the boreholes, in which pumping tests were carried out, is used for both to constrain resistivity inversions and to establish the empirical relationship between the interpreted geophysical and hydraulic parameters. The rest of the boreholes without pumping tests are still used for constraining the inversions. Initially, aquifer parameters were measured using pumping tests at 12 water wells. Afterwards, transmissivity ( T ) and hydraulic conductivity ( K ) were correlated with transverse resistance ( T r ) and the bulk resistivity ( ρ o ) of the aquifer at other sites where pumping tests had not been conducted. In this way, the entire study area was covered to assess the groundwater reserves. The hydraulic properties obtained by the geophysical method fit pretty well to both the pumping and physicochemical data of the investigated area. The integrated study reveals five layers (i.e. topsoil, clay, clay sand, sand and gravel sand) and three potential zones (i.e. high, medium and low potential aquifer zones) with specific ranges of T, K, T r and ρ o . The results suggest that, in case of sparse well data, the aquifer parameters can be estimated using the relations depending on the specifications of the area.